The Internal Image: Mind and Brain in the Age of Charcot. - Schultheiss, Katrin (Modern Intellectual History, 2021)
This article uses the work of French neurologist Jean-Martin Charcot and his contemporaries to explore the central role played by internal or mental images in late nineteenth-century understandings of mental function. It argues that the assumed existence of internal images allowed scientists and clinicians of the time to integrate experimental psychological work on mental pathologies such as memory dysfunction, hysteria, hypnosis, and hallucination into contemporary research on brain physiology. The internal image—a general term that embraced concepts such as "memory images," "sensory images," and multi-faceted "language images"—linked older ideas about how memory, perception, and consciousness worked with new research on cerebral localization that dominated studies of the brain throughout Europe and the United States. For practitioners of the new physiological (also called experimental) psychology, internal images offered a physiological mechanism for explaining how sensory perceptions are transformed into memories, how memories create perceptions of the self, how the brain generates ideas, and how all these processes can go awry.